Advance-Purchase Discounts as a Price Discrimination Device. - Nocke, V; Peitz, M; Rosar, F (Elsevier, 2010)

(untitled)
In an intertemporal setting in which individual uncertainty is resolved over time, advancepurchase discounts can serve to price discriminate between consumers with different expected valuations for the product. Consumers with a high expected valuation purchase the product before learning their actual valuation at the offered advance-purchase discount; consumers with a low expected valuation will wait and purchase the good at the regular price only in the event where their realized valuation is high. We characterize the profitmaximizing pricing strategy of the monopolist. Furthermore, adopting a mechanism design perspective, we provide a necessary and sufficient condition under which advance-purchase discounts implement the monopolist’s optimal mechanism.